Endoplasmic Reticulum Stress‐Induced Apoptotic Effects of Novel 1‐Pyrroline (3, 4‐Dihydro‐2H‐pyrrole) Derivatives on Breast Cancer Cells. Issue 7 (4th July 2022) - Atmaca, Harika; Ilhan, Suleyman; Korkmaz, Esra; Zora, Metin
Abstract: Heterocyclic compounds have emerged as promising and appealing scaffolds for developing effective antitumor agents. Here, the effects of synthesized 24 different 1‐pyrroline derivatives (PDs) containing substituted aryl sulfide moiety were investigated on human breast cancer cell lines. The viability of cells was assessed via MTT assay. Reactive oxygen species (ROS) generation was analyzed via fluorescent dye CM‐H2DCFDA. Apoptotic cells were determined via flow cytometry. Endoplasmic reticulum (ER) stress‐associated protein levels were analyzed via western blot analysis. Four of the PDs (PD‐12, ‐14, ‐16 and ‐17 ) had great cytotoxic selectivity against breast cancer cells. Apoptotic cell death was induced by PDs via the generation of ROS. PDs significantly increased the GRP78, p‐PEAK, p‐eIF2α, and CHOP protein levels indicating ER stress in breast cancer cells. These results imply that newly synthesized PDs may be potential anticancer agents as they selectively inhibit breast cancer cells. Abstract :